Cultural Memory: a position paper - Jukić, Tatjana (2009)
My presentation addressed cultural memory – primarily the concept itself of cultural memory as it emerges in the twentieth century – where it inherits Marxism and psychoanalysis, given that both Marxism and psychoanalysis form precisely around critical interventions into existing memory regimes.